Podcast‐Based Learning in Otolaryngology: Availability, Breadth, and Comparison with Other Specialties. (6th January 2021) - Malka, Ronit; Villwock, Jennifer; Faucett, Erynne A.; Bowe, Sarah
Abstract : Objectives/Hypothesis: Studies across multiple specialties of medical students, residents, and attending physicians demonstrate increased retention, breadth of knowledge, and literature awareness when podcasts are used as an adjunctive educational tool. This Contemporary Review aims to 1) quantify podcast availability and episode frequency for medical learners across a broad range of specialties, and 2) compare these metrics between otolaryngology‐specific podcasts with those of other specialties. Data Sources: Top five podcast platforms: Spotify (Stockholm, Sweden 2006), Apple Podcasts (Cupertino, CA 2012), Google Podcasts (Mountain View, CA 2018), Stitcher (San Francisco, CA 2008), and TuneIn (San Francisco, CA 2002). Methods: The selected podcast platforms were queried with a comprehensive set of keywords and manually searched for medically‐relevant podcasts. Specialty, content, and number of episodes annually for the last 10 years were recorded for each podcast. Results: Otolaryngology has a comparable number of podcasts and breakdown of podcast category compared to other specialties, but reduced total episodes and episode frequency compared to other specialties. This may limit otolaryngologists' ability to engage in this validated form of medical education. Conclusions: Podcast‐based education provides a valuable resource for medical professionals to reinforce learning, broaden general knowledge base, and stay updated on current literature, particularly in light of increased demand for mobile and on‐demand learning options. There is room for an increased number of podcasts and, particularly, increased episode frequency within the field of otolaryngology to extend these benefits to otolaryngologists and otolaryngologists in training. Laryngoscope, 131:E2131–E2138, 2021